Richard F. Salisbury, Reflections on the Integrity of Theory and Praxis. - Feit, Harvey (Culture - Canadian Anthropology Society, 1990)
Richard Salisbury pursued an exceptionally productive career as a scholar, teacher, administrator, applied social scientist, and public figure. By finding a voice and a language with which to speak with coherence to many readerships, his studies provide a bold and innovative model for continued professional elaboration. A core of the possibility for a renewed profession was exemplified in his integrity expressed in a commitment to applying anthropology, theory, and practical knowledge in ways that made them available and accessible to all. His research and advice shaped economic anthropology; the operations of the James Bay Hydro-electric Project; the planning and development of James Bay Cree political institutions, economies and communities; and the development and modernization of post-secondary education in Québec.
Keywords: Richard Salisbury; Theory and Praxis; Engaged Anthropology; Decentralized Development; Aboriginal Rights; Public Policy; James Bay Cree; Public Science